O jogo de xadrez como instrumento de auxílio para o desenvolvimento de competências aos alunos do ensino médio. - Nishimota, Leandro Yoshio (Universidade Federal de São Carlos, 2022)
Chess is a game that stimulates the logical reasoning, spatial vision and critical thinking of practitioners. Several academic studies have already found the affinity between the practice of sport and the development of several skills. This paper deals with the use of the game of chess in the classroom as a tool to aid the competencies that mathematics seeks to develop in secondary school students according to the National Common Curricular Base (BNCC) for high school. For this purpose, research related to teaching was used through the playful to associate math exercises with chess exercises in order to find familiarity between the skills worked and the skills developed, thus producing a bibliographic/qualitative research. The work sought to show the existence of a positive correlation between the competencies established in the BNCC during practice and during the problems involved in the game.
The game of chess as an aid tool for the development of skills to high school students.
Keywords: Xadrez; Jogo; BNCC; Habilidades; Competências; Ensino médio; Matemática; Chess; Game; Skills; Competencies; High school; Mathematics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM